(untitled) (Gaceta Técnica, 2017)
The role of the project manager is one of the most challenging jobs in any organization because it requires a broad understanding of several areas that need to be coordinated and require interpersonal skills. The objective of the work is to define the main competences that must be possessed by the project managers in the construction industry, and also to present how they could develop them. In order to comply with this, a critical analysis was carried out that includes several studies of experts, and institutions dedicated to this area of engineering. This study concludes that the project manager must have the knowledge, skills and attitudes to handle the specific technical aspects, scope, costs, timing and interrelationship, aligned with the objectives, teamwork and stakeholders, among others. All this in a changing, diverse and transversal environment, generating uncertainty and conflicts to be resolved competently